Developing Carbon Nanofibers from Gnetum Gnemon Linn Pericarp Using Dual Activators KOH And Melamine as Innovative Electrode Materials for Supercapacitors - Farma, Rakhmawati; Putri, Hardini Chania; Apriyani, Irma; Azwat, Luqyana Adha; Awitdrus, Awitdrus; Deraman, Mohamad; Rini, Ari Sulistyo; Setiadi, Rahmondia Nanda; Taer, Erman (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Synthesis of carbon nanofibers from Gnetum gnemon Linn (GP) biomass with dual activators, KOH and melamine, offers a potential approach for high-performance supercapacitor electrodes. This study evaluated the preparation of GP-based carbon nanofibers through single and double activation, with varying melamine masses of 0.1, 0.3, and 0.5 g at 0.3 M KOH. The pyrolysis (integrated carbonization and physical activation) occurred at 600°C in N₂ and 800°C in CO₂ atmospheres. The material was activated using 0.3 g of melamine in 0.3 M KOH to produce abundant and highly amorphous nanofiber structures. These characteristics contributed to the high specific capacitance of 400 F/g at a scan rate of 1 mV/s and an energy density of 17 Wh/kg at a power of 465 W/kg. These results demonstrated the synergistic effect of melamine and KOH in increasing the active surface area and structural conductivity. This finding confirms the potential of GP biomass that has not been optimally utilized as a sustainable precursor for energy storage applications, especially supercapacitors.